Computer simulation of tree development with random variations and probabilistic growth of branches - Jinasena, K.D.S.; Sonnadara, D.U.J. (National Science Foundation, 2013)
Abstract: This paper presents the use of self similarity with random variations and probabilistic growth of branches as the basis of generating natural forms of trees. Bifurcation branching geometry has been considered as the fundamental element in the formation of tree structures and Honda’s model was used to generate the recursive branching patterns. In order to simulate the dynamic variations of natural trees, the model was extended by introducing random variation to control the branch lengths and branching angles at each stage. The probabilistic occurrences have been introduced to control the formation of new branches. The resultant tree structures show that the addition of random variation and the introduction of probabilistic occurrence of branches have made a greater impact to the generation of visually convincing natural tree structures.
Keywords: Bifurcation; L-systems; Plant modelling; Stocastic processes